PENGARUH KOMBINASI REBUSAN DAUN CIPLUKAN (Physalis angulata L.) DAN DAUN SALAM (Syzygium polyanthum) TERHADAP KADAR LDL TIKUS PUTIH JANTAN (Rattus norvegicus) - Alinnisa (Universitas Hang Tuah, 2023)
Elevated levels of Low-Density Lipoprotein (LDL) cholesterol can cause plaque on artery walls and be a contributing factor to myocardial infarction. The purpose of this study was to find out the effect of giving water decoction combination of golden berry leaves (Physalis angulate L.) and bay leaves (Syzygium polyanthum) against LDL levels of white rats (Rattus norvegicus) that have induced High-Fat Diet (HFD) and propylthiouracil (PTU). This experimental research study used the pretest-posttest method with a control group design. Use a simple random sampling method with 30 rats. Rats were divided into six treatment groups. Group A was the normal control group, group B was the negative control group, group C combination was 1:1, group D combination was 1:2, group E was 2:1, and group F was the positive control group, treated with simvastatin. LDL cholesterol levels were measured using a spectrophotometer at λ 546 nm. The data will be processed using the One-way ANOVA test followed by Duncan's Post hoc test. There is a significant difference between groups B, C, D, E, and F given HFD and PTU to normal group A. There was a significant reduction in LDL levels in groups C, D, E, and F. The optimal dose of a combination of golden berry leaves and bay leaves that can be given is by a ratio of 1:1 (160mg/200gBB: 720mg/200gBB). The group was given boiled water a combination of golden berry leaves and bay leaves had the effect of lowering LDL levels better than simvastatin. The provision of boiled water a combination of golden berry leaves and bay leaves can lower the LDL levels of male white rats given HFD and PTU. Keywords: Golden Berry Leaf (Physalis angulate L.), Bay Leaf (Syzygium polyanthum), LDL Level, White Rats.